Signs of human right on education: general theoretic analysis - Мельничук, Ольга Федорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In article the looks of scientific in relation to a selection signs of right are analysed to education and anauthorial look is grounded to the problem. With the purpose of the deeper opening of sense of right toeducation, dividing of signs is offered into two groups.